"Stages of change, smoking behavior and acceptability of a textmessaging intervention for tobacco cessation among cigarette, dokha and shishasmokers: A qualitative research study.". Issue 9 (8th September 2019) - Elobaid, Yusra Elhidaia; Jabari, Andrea Leinberger; Al Hamiz, Aisha; Al Kaddour, Abdul Rizzak; Bakir, Sherif; Barazi, Heba; Kazim, Elisa; Sherman, Scott; Ali, Raghib
Abstract : Objectives: To explore: (A) the underlying motivators and barriers to smoking cessation among young Arabic speaking smokers and (B) to examine the suitability and preferences for tobacco cessation interventions (specifically text messages) and study the possibility of enrollment methods for a randomised controlled study using text messages as an intervention for tobacco cessation. Design: Qualitative research using focus group discussions and content analysis. Setting(s): Two universities, one of them is the first and foremost comprehensive national university in the United Arab Emirates (UAE). The third setting is the largest hospital in the UAE and the flagship institution for the public health system in the emirate of Abu Dhabi. Participants: Six focus group discussions with a total of 57 participants. Forty-seven men and 10 women. Fifty-three of them were current smokers. Results: The analysis of six focus groups was carried out. Main themes arose from the data included: preferences for tobacco cessation interventions and acceptability and feasibility of text messaging as tobacco cessation intervention. Different motives and barriers for quitting smoking including shisha and dokha were explored. Conclusion: Interventions using text messaging for smoking cessation have not been used in the Middle East and they could potentially be effective; however, tailoring and closely examining the content and acceptability of text messages to be used is important before the conduction of trials involving their use. Social media is perceived to be more effective and influential, with a higher level of penetration into communities of young smokers.